Efektivitas Pelayanan Pegawai Dalam Tingkat Kepuasan Masyarakat di Kantor Kelurahan Jawa Kecamatan Samarinda Ulu - Jein Natalia; Masjaya; Rita Kalalinggi (Jurnal Ilmu Pemerintahan, 2021)
The purpose of this study is to provide an overview of the actual conditions naturally in employee service to the community at the village office. The results of this study indicate that the Effectiveness of Employee Services in the Level of Community Satisfaction in the Jawa Village Office, Samarinda Ulu District, that employees have implemented services to the community in accordance with SOP (Standard Operating Procedures) but there are still some that have not been carried out in accordance with SOP (Standard Operating Procedures) due to inadequate human resources and infrastructure, so that if it is linked to community satisfaction, it means that community satisfaction is not fully satisfied as a whole based on the research focus. There are still a number of indicators that have not worked out in accordance with the level of community satisfaction related to the Tangibles (Physical Evidence) dimension. Things that are not adequate and are still being complained by the community starting from the sub-district office which is still lacking in staff, discipline in working hours, lack of information disclosure to the public regarding service procedures. Whereas in the Reliability dimension, employees are able to provide services appropriately and correctly and provide quick responses to the community, Responsiveness where employees as service providers always provide clear and directing information and provide solutions for the community as well as assurance that employees provide services according to the needs of the community and responsiveness applies to all communities without being selective, Empathy has been running according to community expectations, namely employees who are attentive, friendly and polite to all members of the public and fellow employees.